Apprendre à enseigner dans le supérieur : quels modèles pour la construction des compétences des universitaires novices ? - Sacha Kiffer (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
How to teach in academia is most often learnt on-the-job (Knight, Tait et Yorke, 2006). But what does the phrase “on-the-job learning” genuinely mean in this case? This article aims to identify which learning practices novice academics make use of to acquire their teaching competences in France. In 2016 a survey carried out among 376 novice lecturers showed that novices’ practices are eclectic and mainly informal. These practices are the reflection of the academic novices’ wish to be autonomous. While public authorities have been developing formal training structures targeted at all newly-hired academics (Le Journal officiel de la République française, 2017), this research suggests that the variety of practices should be taken into account.